KELAYAKAN FINANSIAL NEAR ZERO ENERGY BUILDING DENGAN PERATURAN KEMENTERIAN ENERGI DAN SUMBER DAYA MINERAL NO. 49 TAHUN 2018 MENGENAI INSENTIF ENERGI TERBARUKAN - Ario Bintang Koesalamwardi; Andre Eldrian; Irene; Wellie Tjahyadi (Jurnal Infrastruktur, 2020)
The construction industry and building are responsible for more than 35% of the world's energy consumption and produces almost 40% of greenhouse gas emissions such as CO2. The CO2 emissions come from building energy consumption where more than 65% of them is still generated from fossil fuels. Net Zero-Energy Building (NZEB) is a building system that has high energy efficiency and can generate electricity on-site from renewable energy sources, thereby reducing the operational costs of the annual electricity bill significantly in its whole life cycle. This design concept will add initial construction costs for the application of energy-efficient designs and renewable energy generation systems in buildings. The financial feasibility of a building with this design is measured by a Life Cycle Cost analysis method that also takes into account operational costs over its whole life cycle. Renewable energy incentives are an important factor in financial feasibility analysis because these incentives directly reduce the operational costs (annual electricity costs) of buildings. The Ministry of Energy and Mineral Resources (ESDM) has issued new regulations regarding the amount of incentives given to building owners who install renewable energy generators i.e. Photovolvtaic (PV) panels. There needs to be a study of the financial impact of the issuance of this new regulation on the financial value of NZEB as a whole building system that is integrated with energy generation from PV Panels, especially residential buildings. The purpose of this study is to compare the financial feasibility of NZEB using 2013 regulations, with Ministry of Energy and Mineral Resources Regulation no. 49 of 2018, in dense residential buildings with NZEB design concept. This research concludes the nZEB design is more financialy feasible under the 2013 renewable energy incentive regulation than the 2018 regulation.